2001
DOI: 10.1096/fj.00-0699fje
|View full text |Cite
|
Sign up to set email alerts
|

Indications for a brain‐hair follicle axis: inhibition of keratinocyte proliferation and up‐regulation of keratinocyte apoptosis in telogen hair follicles by stress and substance P

Abstract: It has long been suspected that stress can cause hair loss, although convincing evidence of this has been unavailable. Here, we show that in mice sonic stress significantly increased the number of hair follicles containing apoptotic cells and inhibited intrafollicular keratinocyte proliferation in situ. Sonic stress also significantly increased the number of activated perifollicular macrophage clusters and the number of degranulated mast cells, whereas it down-regulated the number of intraepithelial gd T lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
151
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(163 citation statements)
references
References 57 publications
(78 reference statements)
10
151
0
2
Order By: Relevance
“…3 The neuropeptide substance P (SP) was identified as a key mediator of stress-induced hair growth inhibition, since increased number of SP-immunreactive nerve fibers were present in the skin of stressed mice and hair growth inhibition could be blocked by SP-receptor antagonists. 1,3 This is in line with previous findings that SP is a potent hair growth modulator in mice, since significant changes in the SP skin concentration, as well as in the number of SP-positive sensory nerve fibers are associated with murine hair follicle cycling. 4,5 Taken together, these findings point to the existence of a "brain-hair follicle axis" as a key element in the hair follicle's response to stress, which constitutes a prerequisite for generalized hair loss (telogen effluvium).…”
supporting
confidence: 90%
See 3 more Smart Citations
“…3 The neuropeptide substance P (SP) was identified as a key mediator of stress-induced hair growth inhibition, since increased number of SP-immunreactive nerve fibers were present in the skin of stressed mice and hair growth inhibition could be blocked by SP-receptor antagonists. 1,3 This is in line with previous findings that SP is a potent hair growth modulator in mice, since significant changes in the SP skin concentration, as well as in the number of SP-positive sensory nerve fibers are associated with murine hair follicle cycling. 4,5 Taken together, these findings point to the existence of a "brain-hair follicle axis" as a key element in the hair follicle's response to stress, which constitutes a prerequisite for generalized hair loss (telogen effluvium).…”
supporting
confidence: 90%
“…Tryptase-releasing mast cells can be found in close proximity to PAR-2-expressing cells such as keratinocytes and dermal endothelial cells or C-fibers during inflammation, 70 and we previously reported an increase in SP ϩ nerve fibers in stressed mice and observed that neurogenic inflammation may be abrogated by application of the SP high-affinity neurokinin-1 (NK1) receptor. 1,3 In the present study, cervical and thoracal sensory neurons innervating the dorsal skin were identified by retrograde transport of a tracer dye, subsequently providing insights into SP expression in skinspecific sensory neurons.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…28 -31 Established mouse models to investigate the impact of psychological stress on skin homeostasis are nowadays accessible. 5,32,33 Here, our group and others use the exposure to sound stress, a stress model that has also become appreciated as a highly instructive tool for neuroimmunological stress research beyond the skin. 34 -37 We have now followed-up our previous observations on stress-induced neurogenic skin inflammation by focusing on DCs.…”
mentioning
confidence: 99%